09.36 A tumultuous case of episodic apnoea. Issue 12 (14th November 2019) - Sun, Bo; Mgbachi, Victor; Woodhall, Mark; Voysey, Zanna; Azzopardi, Laura; Rajan, Prabha; Wroe, Stephen; Waters, Patrick; Isabel Leite, M; Irani, Sarosh
Abstract : Glycine-receptor(GlyR) antibodies are well defined in progressive encephalomyelitis with rigidity and myoclonus (PERM), and are associated with a limited spectrum of immunotherapy-responsive syndromes. Whilst paradigms of autoantibody pathogenicity have been proposed, the trigger and propagation of GlyR antibodies remains unclear. We herein describe and define clinical and immunobiological observations of a GlyR antibody positive patient with PERM with the rare association of an ovarian teratoma. A 36-year-old woman presented with subacute axial and limb rigidity, stimulus-sensitive myoclonus, startle, ataxia, anxiety and episodic apnoea. GlyR antibodies were present in serum and CSF. CT revealed a 53 mm left ovarian teratoma. Despite improvement following immunotherapy, she relapsed with respiratory arrest, therefore removal of the left ovarian teratoma was performed. The fresh teratoma tissue was cultured in B-cell stimulating and plasma cell maintaining conditions, based on similar work with ovarian teratomas from patients with NMDAR-antibody encephalitis (Makuch et al., Annals of Neurology 2018).This teratoma secreted GlyR antibodies into culture supernatants consistent with intra-tumoral synthesis of glycine-receptor antibodies. Whilst marked post-surgical improvement was observed, relapses persisted in correspondence with persistent glycine-receptor antibodies. Our case highlights key areas for clinical consideration; GlyR antibody-mediated disease can be paraneoplastic in nature; ovarian teratomas can produce pathogenic autoantibodies; late tumour removal or immunotherapy worsens prognosis.